Enzymatic Enantioselective Decarboxylative Protonation of Heteroaryl Malonates. Issue 17 (12th March 2015) - Lewin, Ross; Goodall, Mark; Thompson, Mark L.; Leigh, James; Breuer, Michael; Baldenius, Kai; Micklefield, Jason
Abstract The enzyme aryl/alkenyl malonate decarboxylase (AMDase) catalyses the enantioselective decarboxylative protonation (EDP) of a range of disubstituted malonic acids to give homochiral carboxylic acids that are valuable synthetic intermediates. AMDase exhibits a number of advantages over the non‐enzymatic EDP methods developed to date including higher enantioselectivity and more environmentally benign reaction conditions. In this report, AMDase and engineered variants have been used to produce a range of enantioenriched heteroaromatic α‐hydroxycarboxylic acids, including pharmaceutical precursors, from readily accessible α‐hydroxymalonates. The enzymatic method described here represents an improvement upon existing synthetic chemistry methods that have been used to produce similar compounds. The relationship between the structural features of these new substrates and the kinetics associated with their enzymatic decarboxylation is explored, which offers further insight into the mechanism of AMDase.